Poly-L-Lysine-Based αGal-Glycoconjugates for Treating Anti-αGal IgE-Mediated Diseases - Olivera-Ardid, Sara; Bello-Gil, Daniel; Tuzikov, Alexander; Araujo, Ricardo N.; Ferrero-Alves, Yara; García Figueroa, Blanca Esther; Labrador-Horrillo, Moisés; García-Pérez, Ana L.; Bovin, Nicolai; Mañez, Rafael (Frontiers in Immunology, 2022)
Anti-αGal IgE antibodies mediate a spreading allergic condition known as αGal-syndrome (AGS). People exposed to hard tick bites are sensitized to αGal, producing elevated levels of anti-αGal IgE, which are responsible for AGS. This work presents an immunotherapy based on polymeric αGal-glycoconjugates for potentially treating allergic disorders by selectively inhibiting anti-αGal IgE antibodies. We synthesized a set of αGal-glycoconjugates, based on poly-L-lysine of different degrees of polymerization (DP1000, DP600, and DP100), to specifically inhibit in vitro the anti-αGal IgE antibodies in the serum of αGal-sensitized patients (n=13). Moreover, an animal model for αGal sensitization in GalT-KO mice was developed by intradermal administration of hard tick’ salivary gland extract, mimicking the sensitization mechanism postulated in humans. The in vitro exposure to all polymeric glycoconjugates (5-10-20-50-100 µg/mL) mainly inhibited anti-αGal IgE and IgM isotypes, with a lower inhibition effect on the IgA and IgG, respectively. We demonstrated a differential anti-αGal isotype inhibition as a function of the length of the poly-L-lysine and the number of αGal residues exposed in the glycoconjugates. These results defined a minimum of 27 αGal residues to inhibit most of the induced anti-αGal IgE in vitro. Furthermore, the αGal-glycoconjugate DP1000-RA0118 (10 mg/kg sc.) showed a high capacity to remove the anti-αGal IgE antibodies (≥75% on average) induced in GalT-KO mice, together with similar inhibition for circulating anti-αGal IgG and IgM. Our study suggests the potential clinical use of poly-L-lysine-based αGal-glycoconjugates for treating allergic disorders mediated by anti-αGal IgE antibodies.